Cyberpatterns Unifying Design Patterns with Security and Attack Patterns - Blackwell, Clive; Zhu, Hong (Springer International Publishing : Imprint: Springer, 2014)
Cyberpatterns are predictable regularities in cyberspace helping us to design and implement more effective and secure systems, and to detect and respond to breaches, failures and deficiencies in operational systems. Cyberpatterns is in its infancy and there are many challenges including: Developing a scientific foundation of pattern-oriented research methods Developing better engineering practice in novel application domains such as for cloud and cyberphysical systems Constructing a sharable knowledge-base to aid education of students, design of novel systems and the development of automated design tools Innovative applications of design patterns to pattern recognition and big data Highlights: Presents the state-of-the-art in the novel field of cyberpatterns Demonstrates the application of patterns to cyber security and other key cyberspace domains Supports the development of a sound scientific, engineering and mathematical foundation for cyberspace This important new book provides an introduction to and coverage of the state-of-the-art of cyberpatterns, from a theoretical standpoint and via practical applications, bringing  together different interdisciplinary areas under one roof to portray a holistic view of the underlying principles and mechanisms of cyberpatterns. Clive Blackwell is an Associate Lecturer at Oxford Brookes University specialising in cyber security and digital forensics Hong Zhu is a Professor at Oxford Brookes University where he is Head of the Applied Formal Methods Research Group. He has a longstanding interest in design patterns and is the author of 'Software design methodology: from principles to architectural styles'.